Analysis of the Virulence of an Atypical Enteropathogenic Escherichia coli Strain In Vitro and In Vivo and the Influence of Type Three Secretion System - Sampaio, Suely C. F.; Moreira, Fabiana C.; Liberatore, Ana M. A.; Vieira, Monica A. M.; Knobl, Terezinha; Romao, Fabiano T.; Hernandes, Rodrigo T. [UNESP]; Ferreira, Claudete S. A.; Ferreira, Antonio P.; Felipe-Silva, Aloisio; Sinigaglia-Coimbra, Rita; Koh, Ivan H. J.; et al. (Hindawi Publishing Corporation, 2014)
Atypical enteropathogenic Escherichia coli (aEPEC) inject various effectors into intestinal cells through a type three secretion system (T3SS), causing attaching and effacing (A/E) lesions. We investigated the role of T3SS in the ability of the aEPEC 1711-4 strain to interact with enterocytes in vitro (Caco-2 cells) and in vivo (rabbit ileal loops) and to translocate the rat intestinal mucosa in vivo. A T3SS isogenic mutant strain was constructed, which showed marked reduction in the ability to associate and invade but not to persist inside Caco-2 cells. After rabbit infection, only aEPEC 1711-4 was detected inside enterocytes at 8 and 24 hours pointing to a T3SS-dependent invasive potential in vivo. In contrast to aEPEC 1711-4, the T3SS-deficient strain no longer produced A/E lesions or induced macrophage infiltration. We also demonstrated that the ability of aEPEC 1711-4 to translocate through mesenteric lymph nodes to spleen and liver in a rat model depends on a functional T3SS, since a decreased number of T3SS mutant bacteria were recovered from extraintestinal sites. These findings indicate that the full virulence potential of aEPEC 1711-4 depends on a functional T3SS, which contributes to efficient adhesion/invasion in vitro and in vivo and to bacterial translocation to extraintestinal sites.